Analysis of Microbial Community in the Archaeological Ruins of Liangzhu City and Study on Protective Materials - Mingliang Sun; Fengyu Zhang; Xinduo Huang; Yeqing Han; Nan Jiang; Biao Cui; Qingling Guo; Mengyue Kong; Lin Song; Jiao Pan (Frontiers in Microbiology, 2020)
This study aims to provide a reference for the protection of the Archaeological Ruins of Liangzhu City. As a basis for the further preservation of these cultural relics, it is essential to analyze the microflora colonizing these soil objects. To do that, samples with microbial characteristics were obtained and analyzed by SEM and metagenomic sequencing to reveal the constitute of the microflora. We investigated the biodegradation of the protective material-epoxy resin by microorganisms in the Archaeological Ruins of Liangzhu City, and found that they would interact with each other, which would affect the performance of the epoxy resin. The specific mechanism of action requires further investigations. We evaluated the effect of ethyl orthosilicate on soil properties. Interestingly, we found that excess ethyl orthosilicate added to the soil of the Archaeological Ruins of Liangzhu City will cause a change in particle size and allowed the soil to condense in the laboratory. This indicates that the large use of orthosilicate may lead to intensified soil weathering, which in turn will cause soil erosion.